2023
DOI: 10.1111/cpr.13541
|View full text |Cite
|
Sign up to set email alerts
|

Notochordal cells: A potential therapeutic option for intervertebral disc degeneration

Yanhu Li,
Haijun Zhang,
Daxue Zhu
et al.

Abstract: Intervertebral disc degeneration (IDD) is a prevalent musculoskeletal degenerative disorder worldwide, and ~40% of chronic low back pain cases are associated with IDD. Although the pathogenesis of IDD remains unclear, the reduction in nucleus pulposus cells (NPCs) and degradation of the extracellular matrix (ECM) are critical factors contributing to IDD. Notochordal cells (NCs), derived from the notochord, which rapidly degrades after birth and is eventually replaced by NPCs, play a crucial role in maintaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 232 publications
0
3
0
Order By: Relevance
“…The main features of IVDD are water molecule loss, ECM degradation, increased fibrosis, and resulting mechanical damage to the disc [ 1 ]. Current research suggests that reducing ROS accumulation and cellular pyroptosis reduces ECM degradation [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main features of IVDD are water molecule loss, ECM degradation, increased fibrosis, and resulting mechanical damage to the disc [ 1 ]. Current research suggests that reducing ROS accumulation and cellular pyroptosis reduces ECM degradation [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Over two-thirds of the global population suffers from neck, shoulder, or lower back pains, which can negatively affect quality of life and health and impose socioeconomic burdens [ 1 ]. Intervertebral disc degeneration (IVDD) is a leading cause of these pains.…”
Section: Introductionmentioning
confidence: 99%
“…Research has demonstrated that notochordal cells play a role in the recovery of IDD. In certain animal models of disc injury, the population of notochordal cells persists even as the animals mature ( Li et al., 2023a ). However, studies have shown that, even in the early stages of human development, there is a significant reduction in viable NP progenitor cells with age.…”
Section: Introductionmentioning
confidence: 99%